Status of Land Rights Built by BUMDES for Internet Connection Poles in Teluk South Purwokerto Village - Rizky Rifai (UM Purwokerto Press, 2023)
Land tenure rights are a set of rules regarding the land that is owned. The installation of poles carried out by BUMDES was built on individual land without licensing or socialization to the landowner. This became a conflict between the landowner and the BUMDES. This research aims to find out what is the status of land on which internet connection poles are built by BMDES and to find out whether landowners can refuse not to build internet connection poles. The method used in this research is normative juridical legal research using Library Research techniques. The research findings reveal that the status of the land in its use is not in accordance with the concept of property rights. So that the owner of the land occupied by the internet connection pole can refuse based on the hierarchy of land tenure.